SUBMICROSCOPIC REORGANIZATION OF RESPIRATORY PULMONARY ALVEOLI AFTER EXPERIMENTAL THERMAL INJURY ALONG WITH COMBINED APPLICATION OF EXOGENOUS SURFACTANT AGENT AND FREEZE-DRIED XENOGRAFT SUBSTRATE - Nebesna, Z.M. (World of Medicine and Biology, 2015)
Submicroscopic state of components of aero-hematic barrier of respiratory portion of lungs after thermal injury has been studied during the experiment, involving white rats, in condition of early necrectomy and application of ground substrate of freeze-dried xenograft and administration of surfactant agent. It has been found that the combined use of such correction agents prevents the development of lesions in the aero-hematic barrier structures and has positive effect on the progress of regenerative processes and their normalization at the late stages of the experiment.
Keywords: aero-hematic barrier; ultrastructural changes; thermal injury; freeze-dried xenograft substrate